Parenting Style and Adolescent Adjustment: Findings of a Cross-Sectional Study in Urban Dhaka (Journal of Preventive and Social Medicine, 2021)
Background: Adolescent adjustment is associated by parenting style as well as influenced by other factors of life. The objective of this study was to assess the association between parenting style and adolescent adjustment.Methods: This cross-sectional study was conducted among 360 adolescents (180 boys and 180 girls) between 15-19 years selected by systematic random sampling from two institutions. Data were collected by semi-structured selfadministered questionnaire after taking informed written consent. The research was conducted in full accord with ethical principles and by keeping in view of the objectives of the study.Results: Among the students, majority (74.2%) were between 15-17 years. The mean (±SD) of age was 16.66 (±1.108). Regarding parenting style, majority, 40.0% parents followed permissive style, 25.8% and 25.3% followed authoritative parenting. Only 8.9%followed negligent parenting. Majority, 59.7% of the adolescent were well adjusted. Parenting style was associated with adolescent adjustment (p